College Instructors' and Students’ Perceptions, Practices, and Assessment of College Students' Critical Thinking Skills in Writing Courses in the UAE - Al Kafri, Banan (2021)
Investigating college English writing instructors and students’ perceptions of effective teaching and assessment methods is of great importance, as it is found that perceptions could highly influence practices of critical thinking. In academic writing courses, the teaching of critical thinking has been even more emphasized as writing activities effectively enhance students’ critical thinking skills. Therefore, the main purpose of this research paper is to investigate how critical thinking is being perceived, practiced, and assessed in college English writing courses. An explanatory mixed methodology has been used. 20 English instructors and 250 students were surveyed using a link for online versions of the teacher and student questionnaires. As for the qualitative part, five classroom observations and six semi-structured interviews were conducted. The findings revealed that college English writing instructors and students have clear and almost similar definitions of critical thinking, yet their perceptions of effective instructional and assessment methods as well as their practices were found to be varied and different. One major mismatch that has been identified between key stakeholders’ perceptions was about the importance of explicit instruction on critical thinking. Based on findings, several recommendations were suggested to policymakers and university administration for more collaborative efforts with instructors to support them in their attempts to teach and assess students’ critical thinking.